Le contrôle des prix et des revenus au Canada - Lipsey, Richard (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractThis paper is a summary of the Legal Factum submitted by the Canadian Labor Congress to the Supreme Court of Canada. It intends to demonstrate the irrelevance of the Anti-Inflationnary Act of October 1975. Three main questions are dealt with.First, was there an economic crisis in October 1975? Analysing various sets of data, the paper concludes that, by no stretch of imagination, could October 1975 be called an economic crisis. Second, was there a policy crisis in the sense that traditional methods had been tried and failed? It establishes here that no serious attempt had been made to contain inflation by traditional fiscal and monetary tools by October 1975. Third, what results can be expected from income policies? This part gives a summary of the voluminous evidence for the U.K. and the U.S., and concludes that the evidence of other incomes policies is that their effects on slowing the rate of inflation are small and often transitory.